Mengukur Dampak Ekonomi Pengelolaan Wisata Terhadap Perekonomian Masyarakat Desa Molotabu: Studi Empiris dan Rekomendasi - Solihin, Dwi Indah Yuliyani; Wahab Podungge, Abdul; Madjid Podungge, Abdul (Jurnal Pemberdayaan Ekonomi dan Masyarakat, 2024)
This article aims to bridge the existing empirical gap by presenting an in-depth and comprehensive analysis of the management of Molotabu Beach and its impact on the economy of the Molotabu Village community using a holistic, participatory, and innovative approach so that this study is expected to formulate policy recommendations and practical strategies that support the development of sustainable tourism in Bone Bolango Regency.The research method was carried out by analyzing empirical study data, namely: 1) a holistic ecological and environmental approach, namely the health of coastal ecosystems related to biodiversity, water quality, and biodiversity; 2) a participatory approach Community involvement in planning and decision-making, and environmental education and awareness programs for the community. Partnerships and collaborations between government, community and private sector; 3) an innovative approach to the use of environmentally friendly technology in beach management. Innovation in waste management, ecotourism and conservation.The results of the study indicate that: 1) The holistic approach shows that although there has been much progress, there are several shortcomings that need to be fixed. Ecological aspects, including waste management and environmental protection, still face challenges. In addition, awareness and support from the village government in management need to be improved to ensure long-term sustainability and effectiveness; 2) Participatory approach in managing tourism objects in Molotabu Village has shown positive results. Active community involvement in planning and decision-making has strengthened the sense of ownership and responsibility for tourism management; 3) The application of an innovative approach in monitoring and evaluation has shown the potential to improve the management of tourism objects in Molotabu Beach